Penerapan Contextual Teaching And Learning (CTL) Dengan Metode Problem Solving Dalam Meningkatkan Hasil Belajar Kajian Kebutuhan Manusia (Pendidikan Ekonomi, 2013)
The purpose of this research is to know the teacher’s activity, student’s activity, student learning’s outcomes, as well as the constraints by application of Contextual Teaching and Learning models with Problem Solving’s method. The Subjects were 23 students of class X TKJ SMK Muhammadiyah 5  Kalitidu.  Research  results  showed  that  teacher’s  activity  at  1st  cycle  was  74.8%,  2nd  cycle  was 84,5% and 3rd cycle was 93.5%. 1st cycle of student’s activity was 51.5%, 2nd cycle was 79.23% and 3rd cycle was 90.8%. Student learning’s outcomes 1st cycle was 65.2%, 2nd cycle was 82.6% and 3rd cycle was 86.95%. Conclusion by applying Contextual Teaching and Learning model with Problem Solving method can increase teacher‘s activity, student activities, and student learning outcomes. Keywords: Contextual Teaching and Learning, Problem Solving, learning outcomes.